Preparation method and application of tantalum-niobium-magnesium-cerium-lanthanum high-entropy alloy / niobium-titanium-oxygen two-phase heterogeneous material

By generating a high-entropy alloy of tantalum niobium magnesium cerium lanthanum in situ on the surface of niobium titanium oxide materials, the problems of lithium dendrites growth at low temperatures and poor electronic conductivity of niobium titanium oxide materials are solved, and efficient low-temperature fast charging performance and cycle stability are achieved.

CN119859825AActive Publication Date: 2025-04-22HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510077344.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-22
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

Traditional graphite negative electrode materials are prone to lithium dendrites to grow at low temperatures, resulting in battery capacity attenuation and poor fast charging performance. The existing niobium titanium oxide materials have problems such as poor electronic conductivity and long diffusion distance of lithium ions, which limit their fast charging performance at low temperatures.

Method used

A two-phase heterogeneous material of tantalum niobium magnesium cerium lanthanum high-entropy alloy/niobium titanium oxooxygen was used to prepare niobium titanium electrodes by traditional high-temperature solid-phase method and tablet sintering method, and a high-entropy alloy was generated on its surface using molten salt electrolysis to improve the electron/ion conductivity and desolvation ability of the material.

Benefits of technology

It significantly improves the first Coulomb efficiency, cycle stability and rate performance of niobium titanium oxide materials at low temperatures, and improves the low-temperature fast charging performance of lithium-ion battery negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859825A_ABST
    Figure CN119859825A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a tantalum-niobium-magnesium-cerium-lanthanum high-entropy alloy / niobium-titanium-oxygen two-phase heterogeneous material, and belongs to the field of secondary batteries, and the preparation method comprises the following specific steps: preparing a compacted titanium niobate electrode by adopting a traditional high-temperature solid-phase method and a tabletting sintering method; the tantalum-niobium-magnesium-cerium-lanthanum high-entropy alloy / niobium-titanium-oxygen two-phase heterogeneous material is prepared by electrolyzing graphite serving as an anode, a tabletting niobium-titanium-oxygen material serving as a cathode and chloride molten salt serving as electrolyte in a tubular furnace. The tantalum-niobium-magnesium-cerium-lanthanum high-entropy alloy / niobium-titanium-oxygen two-phase heterogeneous material is prepared for the first time, the introduced metal alloy can improve the body electron conductivity of the niobium-titanium-oxygen material, and energy band structure rearrangement and electron delocalization at the two-phase interface enhance the adsorption performance of the material surface to solvated lithium, improve the surface / near-surface charge exchange reaction and improve the performance of the material surface to the solvated lithium. The diffusion barrier at a lithium ion interface is reduced, and the first coulombic efficiency and the low-temperature cycling stability of the composite niobium-titanium-oxygen material as a lithium ion battery negative electrode material are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a preparation method and low-temperature application of a tantalum-niobium-magnesium-lanthanum-cerium high-entropy alloy / niobium-titanium-oxide two-phase heterogeneous material. Background Art

[0002] In the electronic information age, electric-powered devices can be seen everywhere, and the demand for energy storage is growing. Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, aerospace, energy storage power stations and other fields due to their high energy density, good cycle stability, clean and pollution-free. However, with the expansion of the lithium-ion battery market, its disadvantage of poor low-temperature performance is particularly prominent. The traditional graphite negative electrode has a low lithium insertion potential (0.1V vs.Li + / Li), it is very easy to have "lithium dendrite" growth at low temperatures, losing active lithium, resulting in rapid battery capacity decay and poor fast charging performance. Therefore, there is an urgent need to explore a lithium-ion battery negative electrode material with good safety, low polarization voltage, high discharge capacity and fast charging characteristics under low temperature environment to promote the development of electrochemical energy storage technology in cold regions.

[0003] Since Goodenough's pioneering work in 2011, niobium titanium oxide (TiNb 2 O 7 ) because its theoretical capacity is close to that of graphite (387 mAh g -1 ), good structural stability and other unique advantages, it has become a research hotspot for high-power negative electrode materials for low-temperature lithium-ion batteries. 2 O 7 Nb(Ti)O is connected by sharing edges or vertices 6 Octahedral composition. Among them, Ti and Nb atoms jointly occupy the 2a and 4i sites of the octahedral gap, forming an open lithium ion transmission channel. Lithium ions are relatively easy to embed / eject during the process, and no obvious volume expansion occurs, showing excellent fast charging characteristics. At the same time, TiNb 2 O 7 Has a higher working potential (1.65Vvs.Li + / Li), which can effectively prevent the formation of solid electrolyte interface layer and lithium dendrites, thus having good safety. However, solid-phase synthesized niobium titanium oxide materials have problems such as small specific surface area, poor electronic conductivity, long lithium ion diffusion distance, slow desolvation process at the electrode-electrolyte interface under low temperature conditions, and high energy barrier for bulk lithium ion diffusion, which limit the fast charging performance of the material under low temperature conditions. Summary of the invention

[0004] Based on the above background technology, the present invention provides a preparation method and low-temperature application of a tantalum-niobium-magnesium-cerium-lanthanum high-entropy alloy / niobium-titanium oxide two-phase heterogeneous material, aiming to improve the electronic / ionic conductivity and desolvation ability of the niobium-titanium oxide material at low temperatures, and improve its electrochemical properties such as the first coulombic efficiency, cycle stability and high-rate performance in low-temperature lithium-ion batteries.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy / niobium-titanium-oxide two-phase heterogeneous material comprises the following steps:

[0007] Step 1: Prepare compacted niobium titanium oxide electrode by conventional high temperature solid phase method and tablet pressing and sintering method;

[0008] Weigh TiO with a molar ratio of 1:1 2 and Nb 2 O 5 Disperse in anhydrous ethanol and mix thoroughly, transfer the mixed sample to a blast drying oven for drying, grind after drying to obtain a powder material precursor A, press the precursor A into a sheet under a certain pressure, called embryo B; transfer embryo B to a tubular furnace, calcine at 1100℃-1400℃, and obtain a white compacted sheet niobium titanium oxide electrode after cooling to room temperature;

[0009] The mixing method is mechanical stirring, magnetic stirring or ball milling, the stirring or ball milling time is 4-10 hours, and the ball milling speed is 300-500r / min;

[0010] The pressure for preparing the embryo B is 120-180 MPa, and the thickness of the pressed sheet is 2-5 mm; preferably, the embryo B is a Φ9 mm round sheet.

[0011] The calcination time in the tubular furnace is 1-30h;

[0012] Step 2: In-situ generation of a tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy / niobium-titanium oxide two-phase heterogeneous material on the surface of the niobium-titanium oxide material by molten salt electrolysis;

[0013] Using the flake niobium titanium oxide prepared in step 1 as a cathode, graphite as an anode, and chloride molten salt as a molten salt electrolyte, applying voltage to the two electrodes at a certain temperature to perform molten salt electrolysis, taking out the cathode product obtained after the electrolysis after the electrolysis, collecting it by centrifugation, drying it at a low temperature and grinding it to obtain a tantalum niobium magnesium cerium lanthanum high entropy alloy / niobium titanium oxide two-phase heterogeneous material;

[0014] Among them, chloride soluble salts include NaCl, KCl, TaCl 5 、NbCl 5 MgCl 2 、CeCl3 and LaCl 3 The mass of NaCl and KCl in chloride molten salt is equal and the mass of the two accounts for 70%-84% of the chloride molten salt. 5 、NbCl 5 MgCl 2 、CeCl 3 and LaCl 3 The masses of the five components are equal and the total amount of the five components accounts for 16%-30% of the chloride soluble salt;

[0015] The temperature of molten salt electrolysis is 700-1000°C; the electrolysis time is 2-8h; and the constant voltage applied during the electrolysis process is 0.5-2.4V.

[0016] The protective atmosphere of the molten salt electrolysis furnace is a mixed gas of hydrogen and argon (the volume ratio of argon and hydrogen is 95%:5%), argon, nitrogen or one of the following;

[0017] The centrifugal speed is 5000-9000r / min, and the centrifugal time is 3-6 minutes each time;

[0018] An application of a tantalum, niobium, magnesium, cerium, lanthanum high entropy alloy / niobium titanium oxide two-phase heterogeneous material prepared by the preparation method, wherein the tantalum, niobium, magnesium, cerium, lanthanum high entropy alloy / niobium titanium oxide two-phase heterogeneous material is used as a negative electrode material in a low-temperature lithium-ion battery.

[0019] The tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy / niobium-titanium oxide two-phase heterogeneous material is dispersed in a solvent with a conductive agent and a binder in a certain mass ratio as a negative electrode active material to obtain a negative electrode slurry for a lithium-ion battery. The negative electrode slurry is evenly coated on a negative electrode collector, dried, rolled, and punched to obtain a negative electrode sheet, and then button batteries are assembled.

[0020] The binder is polyvinylidene fluoride (PVDF) or an aqueous dispersion of acrylonitrile multi-polymer (LA133), the conductive agent is acetylene black, and the solvent is N-methylpyrrolidone (NMP) or ultrapure water.

[0021] The mass ratio of the negative electrode active material: the conductive agent: the binder is 85%: 7.5%: 7.5%.

[0022] The operating temperature range of the low-temperature lithium-ion battery is -40°C to 60°C.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1) The present invention is the first to use chloride molten salt as an electrolyte to carry out electrolysis in a tubular furnace to prepare a tantalum, niobium, magnesium, cerium, lanthanum high entropy alloy, and obtain a tantalum, niobium, magnesium, cerium, lanthanum high entropy alloy / niobium titanium oxide two-phase heterogeneous material. The introduced metal alloy can improve the bulk electronic conductivity of the niobium titanium oxide material, and the band structure rearrangement and electron delocalization at the interface between the two phases enhance the adsorption performance of the material surface for solvated lithium, improve the surface / near-surface charge exchange reaction, and reduce the diffusion barrier at the lithium ion interface, so that the material still has a high lithium ion diffusion coefficient under low temperature conditions, greatly improving the first coulombic efficiency of the composite niobium titanium oxide material as a negative electrode material for lithium ion batteries and the cycle stability at low temperatures.

[0025] 2) The preparation method of the present invention is simple, has a coherent process, is low in cost, has low requirements on equipment, and is suitable for large-scale production.

[0026] 3) The present invention uses TaCl 5 、NbCl 5 MgCl 2 、CeCl 3 and LaCl 3 The combination of is used as an electrolyte to in-situ form a tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy on the surface of niobium-titanium oxide. The composition of the alloy prepared by the present invention has a stable phase diagram, and during the synthesis process, it can be ensured that no other forms of compounds can exist stably. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the synthesis of the tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy / niobium-titanium-oxide two-phase heterogeneous material synthesized in Example 1;

[0028] Figure 2 This is an EIS comparison chart of the tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy / niobium-titanium oxide two-phase heterogeneous material and the pure-phase niobium-titanium oxide material at -40°C synthesized in Example 1;

[0029] Figure 3 This is a comparison chart of the cyclic stability at -40°C of the tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy / niobium-titanium oxide two-phase heterogeneous material and the pure-phase niobium-titanium oxide material synthesized in Example 1. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] Embodiment 1:

[0032] A method for preparing a tantalum-niobium-magnesium-lanthanum-cerium high entropy alloy / niobium-titanium-oxide two-phase heterogeneous material, comprising the following steps:

[0033] Step 1: Prepare compacted niobium titanium oxide electrode by conventional high temperature solid phase method and tablet pressing sintering method; 0.16g TiO 2 and 0.53 g of Nb 2 O 5 Dispersed in 30 mL of anhydrous ethanol, mechanically stirred for 6 hours, the mixed sample was transferred to a blast drying oven for drying, and after drying, the powder material precursor A was obtained by grinding, and the precursor A was pressed into a 3 mm round piece with a diameter of Φ9 mm under a pressure of 150 MPa, which was called embryo B; embryo B was transferred to a tubular furnace and calcined at 1300 ° C in a tubular furnace, and a white compacted sheet-like niobium titanium oxide electrode was obtained after cooling to room temperature;

[0034] Step 2: In situ generate a tantalum-niobium-magnesium-cerium-lanthanum high-entropy alloy / niobium-titanium oxide two-phase heterogeneous material on the surface of the niobium-titanium oxide material by molten salt electrolysis; use the flaky niobium-titanium oxide electrode prepared in step 1 as the cathode, graphite as the anode, and NaCl-KCl-TaCl 5 -NbCl 5 -MgCl 2 -CeCl 3 -LaCl 3 It is a molten salt electrolyte with a mass ratio of NaCl:KCl:TaCl 5 :NbCl 5 MgCl 2 :CeCl 3 :LaCl 3 =35%:35%:6%:6%:6%:6%:6%:6%, the constant voltage applied to the two electrodes is 2.0V, the molten salt electrolysis is carried out at 800℃ for 5h, the cathode product obtained after the electrolysis is taken out, the above solution is centrifuged with anhydrous ethanol and distilled water, and the centrifugation is carried out three times at a speed of 6500 rpm, each time for 3 minutes, the product is collected, dried and ground at low temperature to obtain tantalum niobium magnesium cerium lanthanum high entropy alloy / niobium titanium oxide two-phase heterogeneous material. The schematic diagram of the preparation of tantalum niobium magnesium cerium lanthanum high entropy alloy / niobium titanium oxide two-phase heterogeneous material is shown in the figure Figure 1 As shown, the high entropy alloy is uniformly grown on the niobium titanium oxide material through molten salt electrolysis.

[0035] The tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy / niobium-titanium-oxide two-phase heterogeneous material obtained in this embodiment is applied to the negative electrode of a low-temperature lithium-ion battery to improve the cycle stability and rate performance of the battery at low temperatures.

[0036] The prepared tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy / niobium-titanium oxide two-phase heterogeneous material, binder polyvinylidene fluoride (PVDF), and conductive agent acetylene black were dispersed in N-methylpyrrolidone (NMP) solvent at a mass ratio of 85%:7.5%:7.5% to obtain a negative electrode slurry, which was coated on the negative electrode collector, dried, rolled, and punched to obtain a negative electrode sheet, and then button batteries were assembled to test the electrochemical performance. The EIS curve at minus 40°C is shown in Figure 1. Figure 2 As shown in the figure, compared with pure phase niobium titanium oxide material, the tantalum niobium magnesium cerium lanthanum high entropy alloy / titanium niobate two-phase heterogeneous material electrode also shows lower charge transfer resistance at low temperature, indicating that it has better kinetic properties and is conducive to showing excellent low-temperature fast charging performance. The cycling performance at -40℃ and 0.5C is shown in the figure. Figure 3 As shown, the activation discharge capacity at 0.2C is 129.8 mAh g -1 , the charging capacity is 125.9mAh g -1 The first coulombic efficiency is 96.9%; the first cycle discharge capacity at 0.5C is 82.2mAh g -1 Even at the 100th cycle, the discharge capacity is 112.6 mAh g -1 , charge capacity 111.5mAh g -1 , much higher than pure phase niobium titanium oxide materials (90.6 / 90.2mAhg -1 ), indicating that the lithium-ion battery assembled using the present invention has good low-temperature cycle performance.

[0037] Example 2

[0038] The differences between the present embodiment and the embodiment 1 in preparing the tantalum-niobium-magnesium-cerium-lanthanum high entropy alloy / niobium-titanium-oxide two-phase heterogeneous material are as follows: the pressure for preparing the embryo B is 120 MPa, and the thickness of the pressed sheet is 2 mm; the high-temperature calcination time of the embryo B is 1200°C for 15 h; the mass ratio of the molten salt electrolyte is

[0039] NaCl:KCl:TaCl 5 :NbCl 5 MgCl 2 :CeCl 3 :LaCl 3 =40%:40%:4%:4%:4%:4%:4%:4%, and other parameters are the same as those in Example 1.

[0040] Example 3

[0041] The differences between the preparation of tantalum-niobium-magnesium-cerium-lanthanum high-entropy alloy / niobium-titanium oxide two-phase heterogeneous material in this embodiment and that in embodiment 1 are as follows: the stirring method of precursor A is ball milling, the ball milling speed is 300r / min, and the time is 4h; the pressure for preparing embryo B is 120MPa, and the tablet thickness is 4mm; the high-temperature calcination time of embryo B is 1250℃, and the time is 18h; the mass ratio of molten salt electrolyte is NaCl:KCl:TaCl 5 :NbCl 5 MgCl 2 :CeCl 3 :LaCl 3 =40%:40%:4%:4%:4%:4%:4%:4%, and other parameters are the same as those in Example 1.

[0042] Example 4

[0043] The differences between the preparation of tantalum-niobium-magnesium-cerium-lanthanum high-entropy alloy / niobium-titanium oxide two-phase heterogeneous material in this embodiment and that in embodiment 1 are as follows: the stirring method of precursor A is ball milling, the ball milling speed is 300r / min, and the time is 4h; the pressure for preparing embryo B is 110MPa, and the thickness of the pressed sheet is 3mm; the high-temperature calcination time of embryo B is 1250℃, and the time is 20h; the mass ratio of molten salt electrolyte is NaCl:KCl:TaCl 5 :NbCl 5 MgCl 2 :CeCl 3 :LaCl 3 =40%:40%:4%:4%:4%:4%:4%:4%, and other parameters are the same as those in Example 1.

[0044] Example 5

[0045] The preparation of tantalum-niobium-magnesium-cerium-lanthanum high-entropy alloy / niobium-titanium oxide two-phase heterogeneous material in this embodiment is different from that in embodiment 1 in that: the stirring method of precursor A is ball milling, the ball milling speed is 400r / min, and the time is 4h; the pressure for preparing embryo B is 140MPa, and the thickness of the tablet is 2mm; the mass ratio of the molten salt electrolyte is NaCl:KCl:TaCl 5 :NbCl 5 MgCl 2 :CeCl 3 :LaCl 3 =40%:40%:4%:4%:4%:4%:4%; the constant voltage applied during the electrolysis process is 0.8V, and the other parameters are the same as in Example 1.

[0046] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a tantalum-niobium-magnesium-lanthanum-cerium high entropy alloy / niobium-titanium-oxide two-phase heterogeneous material, characterized in that: The following steps are involved: Step 1: Prepare niobium titanium oxide electrode by conventional high temperature solid phase method and tablet pressing and sintering method; Step 2: Using a niobium titanium oxide electrode as a cathode, graphite as an anode, and a chloride molten salt as a molten salt electrolyte, after assembly, applying voltage to the two electrodes to perform molten salt electrolysis, taking out the cathode product obtained after electrolysis, collecting it by centrifugation, and drying and grinding it at a low temperature to obtain a tantalum niobium magnesium cerium lanthanum high entropy alloy / niobium titanium oxide two-phase heterogeneous material; Among them, chloride soluble salts include NaCl, KCl, TaCl5, NbCl5, MgCl2, CeCl3 and LaCl3.

2. The preparation method according to claim 1, characterized in that: In step 2, the protective atmosphere of the molten salt electrolysis reaction is a mixed gas of argon and hydrogen, argon or nitrogen.

3. The preparation method according to claim 1, characterized in that: In step 2, the masses of NaCl and KCl in the chloride molten salt are equal and their total mass accounts for 70%-84% of the chloride molten salt, and the masses of the five components TaCl5, NbCl5, MgCl2, CeCl3 and LaCl3 are equal and their total mass accounts for 16%-30% of the chloride molten salt.

4. The preparation method according to claim 1, characterized in that: In step 2, the temperature of molten salt electrolysis is 700-1000°C and the time is 2-8h.

5. The preparation method according to claim 1, characterized in that: In step 2, the constant voltage applied during the molten salt electrolysis process is 0.5-2.4V.

6. The preparation method according to claim 1, characterized in that: In step one, the specific method for preparing the niobium titanium oxide electrode is as follows: TiO2 and Nb2O5 with a molar ratio of 1:1 are dispersed in anhydrous ethanol and mixed thoroughly, the mixed sample is dried, and a powder material precursor A is obtained by grinding, the precursor A is pressed into sheets, and the sheets are transferred to a tubular furnace for calcination at 1100°C-1400°C to obtain a white compacted sheet-like titanium niobate electrode.

7. The preparation method according to claim 6, characterized in that: The precursor A is pressed into a sheet at a pressure of 120-180 MPa with a thickness of 2-5 mm.

8. The preparation method according to claim 6, characterized in that: The calcination treatment time in the tubular furnace is 1-30h.

9. An application of a tantalum-niobium-magnesium-lanthanum-cerium high entropy alloy / niobium-titanium-oxide two-phase heterogeneous material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The tantalum-niobium-magnesium-lanthanum-cerium high entropy alloy / niobium-titanium-oxide two-phase heterogeneous material is used as a negative electrode active material in the negative electrode of a low-temperature lithium-ion battery.

10. The use according to claim 9, characterized in that: The operating temperature range of the low-temperature lithium-ion battery is -40°C to 60°C.

Citation Information

Patent Citations

  • Preparation method and usage method of core-shell heterostructure composite material

    CN109449392A

  • Active electrode material

    CN114868278A

  • Positive Electrode Active Material for Lithium Secondary Battery, Method of Preparing the Same, and Positive Electrode for Lithium Secondary Battery and Lithium Secondary Battery which Include the Positive Electrode Active Material

    US20200280065A1